Income Disparity between Japan and ASEAN-5 Economies: Converge, Catching Up or Diverge? - Hock-Ann Lee; Kian-Ping Lim; M. Azali (-, 2005)
The objective of this study is to empirically examine the income disparity between Japan and each of the five major economies of South East Asia (ASEAN−5) during the period of 1960 to 1997, utilizing the popular augmented Dickey−Fuller (ADF) unit root test. The results provide evidence of income divergence between Japan and each of the ASEAN−5 economies. To avoid the problem associated with structural break, this study proceeds with the jointly crash and changes in trend model proposed by Zivot and Andrews (1992), and is able to obtain evidence of long run income convergence between the Japanese and Singaporean economies. As for the rest of the four ASEAN countries− Indonesia, Malaysia, the Philippines and Thailand, the earlier results of income divergence remain valid and hence suggest that it would be a more realistic and urgent goal to narrow the income gap among these five core economies of ASEAN.